Corporate Sustainability:: A Case Study at Mãe de Deus Hospital (Sustainability in Debate, 2015)
This paper aims to analyze the pillars of sustainability contemplated in the management modelof the Mãe de Deus Hospital, located in Porto Alegre, Rio Grande do Sul, Brazil. This qualitativeand descriptive research is based on a case study seeking to highlight the pillars of sustainabilitymanagement based on organizational practices. Data were collected through semi-structuredinterviews conducted with nine hospital executives and were analyzed using qualitative contentanalysis with N-Vivo software support. Main results show that since 2000 the concept of corporatesustainability has been embedded in business management models that consider economicand social pillars as a part of the decision-making process. These relevance of these pillars relyupon several factors, such as: a) economic factors ”“ the need for the self-sustainability of thehospital network; b) social factors - the nature of business and the mission of the religious congregation,which is based on humanization values.